Pemanfaatan Tanah sebagai Jaminan Praktik Qard dalam Tinjauan Ekonomi Syari’ah: Studi di Desa Somalang, Kecamatan Pakong, Kabupaten Pamekasan, Madura - Abdussakur Abdussakur (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2021)
Some Madurese people realize that the tradition of credit guaranteed by land use has several negative impacts. Apart from being contrary to al-Qur’an and Hadith, this tradition is also detrimental to the community because it results the guarantee provider is no longer being able to take advantage of it. The people of Somalang, Pakong, Pamekasan, Madura are with the tradition of credit guaranteed by land use until now. Actually, there are a number of people who do not agree with this tradition. However, their arguments are often lacking in strength. Considering that this tradition has been running for decades, so it cannot be separated from the live of the Madurese in general and the Somalang people in particular. This is a descriptive qualitative research and using a case study approach. Based on the result of this study, it can be concluded that the tradition of credit guaranteed by land use in Somalang is less profitable for the second party as the recipient of the guarantee. So that, in addition to injure the actual system of credit, this tradition also contradicts the shariah concept of tradition, credit, and the taking of benefit from the land as a guarantee.